Advanced electrical machine design for azimuthing electrical podded propulsor - Chu, Kin Hey (2017)
At present, energy efficiency, operational reliability and cost savings are some of the most important factors regarding electrical systems in marine business industry. Regulations such as the International Marine Organization (IMO) Tier III impose a tougher limit to global warming emissions than before. The permanent magnet synchronous machines (PMSMs) are great contenders for electrical machine propulsion. They are highly efficient, lightweight and compact. However, due to the high cost of rare earth elements (REE), PMSM is substantially more costly than most machines of other topologies. Unfortunately, no readily available substitute exists for most REE. In the doctoral thesis, a study of hybrid excitation synchronous machine (HESM) is presented. HESMs are synchronous machines, where the total rotor field excitation is produced by the simultaneous action of electrical and permanent magnet (PM) excitation. This study contributes a more efficient alternative for the brushless excited synchronous machine (BLSM) which meets all the requirements for azimuthing podded propulsion. A literature review was conducted to understand the trends in the podded propulsor market and electrical machines topologies suitable for marine propulsion. The HESM was found to be a potential alternative to the BLSM. An overview of published HESM designs is given from a standpoint of complexity of design, energy efficiency, cost, manufacturability, etc. The feasibility study narrowed down the possible designs of HESM for traction/propulsion applications. Based on analytical methods, a program was written for the preliminary calculations of the machine dimensions and its main parameters. The design is refined using Ansys-RMxprt software followed by finite element method (FEM) software, Ansys-Maxwell. Throughout the stages, the machine designs were optimized. Electromagnetic simulations are applied to the final machine designs to obtain design parameters, electromagnetic forces and machine characteristics. Thermal analyses and economy studies are also performed. A benchmark 5MW BLSM is developed to replicate the existing electric machine used in the application.Two variants of HESMs are developed, one of them with additional armature reaction compensation capability. The performances of the HESMs were found to be superior to that of the BLSM. An experiment was carried out to verify the armature reaction compensation technique. Two commercially available 12.5kVA, 4-pole wound field synchronous machines were used. One of the machines is modified to incorporate magnets on one edge of each pole. The other machine is left unmodified to act as a benchmark for the experiment. The experimental results along with FEM simulations show improvements to the machine performance brought about by the proposed technique. Efficiency of electrical machines tends to increase with their sizes. Therefore, there is a power rating limit to which the benefit of higher efficiency can be achieved by this technology. However, when used in low power applications as in this case, the increase in machine efficiency can be quite substantial. Limited by economy, this technology is most feasible for the azimuthing podded propulsor at power levels where the application of PMSM is too expensive and BLSM is not sufficiently energy efficient.